2018
DOI: 10.1186/s12888-018-1920-7
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic outcomes in treatment resistant depression: a secondary analysis of the STAR*D study

Abstract: BackgroundIn the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study, a third of patients did not achieve remission or adequate response after two treatment trials, fulfilling requirements for treatment resistant depression (TRD). The present study is a secondary analysis of the STAR*D data conducted to compare the humanistic outcomes in patients with TRD and non-TRD MDD.MethodsPatients with major depressive disorder who entered level 3 of the STAR*D were included in the TRD group, while pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 32 publications
5
28
1
7
Order By: Relevance
“…The levels of absenteeism, presenteeism, overall work productivity loss and activity impairment associated with ED in the current study (7.1%, 22.5%, 24.8% and 28.6%, respectively) were comparable to those reported in prior research on treatment resistant depression, obesity and type 2 diabetes mellitus . The levels of HRQoL observed in the current study among men with ED (46.7, 48.3 and 0.693 for the Mental Component Summary, Physical Component Summary and SF‐6D, respectively) were likewise in line with the aforementioned conditions.…”
Section: Discussionsupporting
confidence: 89%
“…The levels of absenteeism, presenteeism, overall work productivity loss and activity impairment associated with ED in the current study (7.1%, 22.5%, 24.8% and 28.6%, respectively) were comparable to those reported in prior research on treatment resistant depression, obesity and type 2 diabetes mellitus . The levels of HRQoL observed in the current study among men with ED (46.7, 48.3 and 0.693 for the Mental Component Summary, Physical Component Summary and SF‐6D, respectively) were likewise in line with the aforementioned conditions.…”
Section: Discussionsupporting
confidence: 89%
“…In the STAR*D study, participants reported high unemployment rates, ranging from 36% for patients who responded to step 1 treatment to 47% for patients who progressed to step 4 [ 5 ]. In another STAR*D analysis, patients with treatment-resistant depression demonstrated lower vocational productivity than patients with non–treatment-resistant major depressive disorder [ 31 ]. A claims-based study found that employees with treatment-resistant depression had an average of 35.8 work loss days per year, which was 1.7 times the rate of work loss days in employees with non–treatment-resistant major depressive disorder and 6.2 times that of those without major depressive disorder [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one clinical study, TRD out-patients incurred higher costs than other depressed patients related to the number of working days lost, and these costs did not correlate with depression severity [24]. Also, a recent re-analysis of data from the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) trial showed greater functional and work impairment as well as lower work productivity among the patients classified with TRD compared to other depressed patients [25].…”
Section: Introductionmentioning
confidence: 99%